Release of Non-Exchangeable Potassium in Some Acidic Terai Soils of Himalayan Floodplain - D. Mukhopadhyay; A. Patra, N.K. Singh, G.C. Banik* (Journal of the Indian Society of Soil Science, 2021)
Non-exchangeable potassium (K) reserve and its release pattern is an important issue to optimize the K-fertilization for crops in long-term. The non-exchangeable K release in terms of Step-K and Constant rate-K was measured by repeated extraction of soil with boiling 1 N HNO3 in surface (0-20 cm) and sub-surface (20-40 cm) soil of six different blocks of Cooch Behar district situated in Himalayan floodplain of northern part of West Bengal. The non-exchangeable K content was found adequate in surface soils. Step-K and Constant rate-K were dependent on organic carbon, CEC and soil texture. The cumulative release of non-exchangeable K showed semi-logarithmic behaviour with increasing number of extractions with a highly significant correlation coefficient and suggested the progressive decrease in release of non-exchangeable K with sequential extraction. The threshold-K level for release of intermediate K and Gapon constant (KG) of surface soils were found to vary with the change of background electrolyte concentration for all soils and suggests the tenacity with which K is specifically held in the wedge zones of the clays present in these soils.